Application of Demonstration Methods in Community Service Activities to Improve Psychomotor of Diesel Engine for Vocational School Students in Agam - Sugiarto, Toto Sugiarto; Purwanto, Wawan; Arif, Ahmad (Universitas Negeri Padang, 2022)
Vocational High Schools (SMK) aims to be able to prepare students who are creative, master science and technology, and have competencies in accordance with the demands of the world of work. SMK students are designed to have high psychomotor abilities in accordance with the demands of the world of work. This paper aims to describe the application of the demonstration method in improving the psychomotor abilities of vocational school students in community service activities. This method is applied in training activities to increase vocational competency in diesel engine technology. With stages students are guided to identify diesel engine components and parts, start a diesel engine, identify diesel motor support systems and carry out diesel motor maintenance. The results of observations show that the direct demonstration method can improve students psychomotor abilities in the field ofdiesel engine technology. The demonstration method that has been applied is able to improve students psychomotorskills. At the first meeting the students scores were still low, but after guidance and demonstration was carried out, in the second and third observations the students had increased, students were more confident in doing maintenance work on a 4 stroke 1 cylinder diesel engine.